Rehabilitation Ethics Codes in English-Speaking Countries: A Narrative Review - Ebrahim Sadeghi-Demneh; saeed forghany (Vesnu Publications, 2019)
Introduction: Rehabilitation of people with disability has ethical dimensions. Therefore, the aim of this study was to review the codes of ethics for rehabilitation in English-speaking countries through a narrative review. Materials and Methods:  In this study, the ethical codes in Australia, Canada, the Unite States, and the United Kingdom were searched electronically through the google search engine, because the language was understandable for researchers. Accordingly, the codes of ethics for rehabilitation (including Orthotics and Prosthetics, occupational therapy, and physiotherapy) were extracted and studied by two researchers independently. Results: A set of professional responsibilities for the rehabilitation services were categorized according to four principles of biomedical ethics and presented as ethical codes for rehabilitation services. Conclusion: As the first step in developing a reliable framework for professional ethics, professional ethics codes for rehabilitation in Australia, Canada, the United States, and the United Kingdom were reviewed through a narrative review, in order to provide the basis for professional ethics in rehabilitation services based on Iranian Islamic teachings.